2016
DOI: 10.1021/acs.nanolett.6b01240
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Epitaxial Silicon Solar Cells with Inverted Nanopyramid Arrays for Efficient Light Trapping

Abstract: Ultrathin c-Si solar cells have the potential to drastically reduce costs by saving raw material while maintaining good efficiencies thanks to the excellent quality of monocrystalline silicon. However, efficient light trapping strategies must be implemented to achieve high short-circuit currents. We report on the fabrication of both planar and patterned ultrathin c-Si solar cells on glass using low temperature (T < 275 °C), low-cost, and scalable techniques. Epitaxial c-Si layers are grown by PECVD at 160 °C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 45 publications
(86 reference statements)
2
59
1
Order By: Relevance
“…They noted that the LTE of experimental cells is significantly lower than that of theoretical structures, which can approach the Lambertian limit, LTE=1. The present nanophotonic cell, and that of [14], present a clear improvement compared to the reported results of [37], by advancing from 0.2-0.3 to 0.56 and 0.57 respectively. We further focus on the lowly-absorbed photons and evaluate the light-path enhancement factor of the nanophotonic cells following the same method as in [14].…”
supporting
confidence: 38%
See 3 more Smart Citations
“…They noted that the LTE of experimental cells is significantly lower than that of theoretical structures, which can approach the Lambertian limit, LTE=1. The present nanophotonic cell, and that of [14], present a clear improvement compared to the reported results of [37], by advancing from 0.2-0.3 to 0.56 and 0.57 respectively. We further focus on the lowly-absorbed photons and evaluate the light-path enhancement factor of the nanophotonic cells following the same method as in [14].…”
supporting
confidence: 38%
“…The present nanophotonic cell, and that of [14], present a clear improvement compared to the reported results of [37], by advancing from 0.2-0.3 to 0.56 and 0.57 respectively. We further focus on the lowly-absorbed photons and evaluate the light-path enhancement factor of the nanophotonic cells following the same method as in [14]. The factor F estimates the light-path enhancement by using a simple model of propagation of diffracted waves [38,39].…”
supporting
confidence: 38%
See 2 more Smart Citations
“…was investigated both experimentally and numerically and broadband absorption enhancement of solar radiation was demonstrated. 5,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Photovoltaic cells based on subwavelength features were experimentally realized with carrier extraction schemes such as all back-side contacts, radial congurations in which the p-n junction is aligned in a core-shell geometry, and axial congurations where the junction is positioned along the height of the subwavelength structure. 28,29,41,42,[44][45][46] Kayes et al presented a model for pillar arrays with radial junctions and demonstrated carrier extraction enhancement due to the short collection lengths.…”
Section: Introductionmentioning
confidence: 99%